Developing successful ICT strategies : competitive advantages in a global knowledge-driven society - Rahman, Hakikur, 1957- (Hershey, PA : Information Science Reference, 2008)
'This book collects an authoritative core of research investigating the notion that information communication technologies (ICTs) have the potential to improve the lives of people and contribute to enhancing social conditions in developing countries through such concepts as the Knowledge Society, open education, and e-governance'--Provided by publisher.
'Premier reference source'--Cover.
Includes bibliographical references (p. 357-389) and index.
Keywords: Information technology -- Developing countries; Technological innovations -- Developing countries; Information technology -- Economic aspects -- Developing countries; Technological innovations -- Economic aspects -- Developing countries; Knowledge management